2021
DOI: 10.3390/nano11030569
|View full text |Cite
|
Sign up to set email alerts
|

Artificial Cathode-Electrolyte Interphase towards High-Performance Lithium-Ion Batteries: A Case Study of β-AgVO3

Abstract: Silver vanadates (SVOs) have been widely investigated as cathode materials for high-performance lithium-ion batteries (LIBs). However, similar to most vanadium-based materials, SVOs suffer from structural collapse/amorphization and vanadium dissolution from the electrode into the electrolyte during the Li insertion and extraction process, causing poor electrochemical performance in LIBs. We employ ultrathin Al2O3 coatings to modify β-AgVO3 (as a typical example of SVOs) by an atomic layer deposition (ALD) tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Resultantly any transformation in capacitance will show up in the Bode plots with a considerably stronger signature. Given their higher sensitivity to fluctuations in capacitance, Bode diagrams are deemed more suitable for elucidating capacitances and pseudocapacitances, as noted in previous studies [70] …”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Resultantly any transformation in capacitance will show up in the Bode plots with a considerably stronger signature. Given their higher sensitivity to fluctuations in capacitance, Bode diagrams are deemed more suitable for elucidating capacitances and pseudocapacitances, as noted in previous studies [70] …”
Section: Resultsmentioning
confidence: 94%
“…Given their higher sensitivity to fluctuations in capacitance, Bode diagrams are deemed more suitable for elucidating capacitances and pseudocapacitances, as noted in previous studies. [70]…”
Section: Photoelectrochemical Investigationsmentioning
confidence: 99%
“…Therefore, Bode diagrams are better suited for illustrating changes in capacitance and pseudocapacitance. For capacitance and pseudocapacitance description, Bode diagrams are preferred [72] . EIS of α‐La 2 S 3 in a published research showed an impressive Rs of 0.17 Ω.…”
Section: Resultsmentioning
confidence: 99%
“…For capacitance and pseudocapacitance description, Bode diagrams are preferred. [72] EIS of α-La 2 S 3 in a published research showed an impressive Rs of 0.17 Ω. This low level of resistance is due to the low intrinsic resistance improving the redox activity of the electrode during charge-discharge.…”
Section: Chemistryselectmentioning
confidence: 94%